PEMBERDAYAAN MASYARAKAT AKADEMIK MELALUI WORKSHOP ANALISIS STRUKTUR PENYUSUNAN RKUHAP BERBASIS REGULATORY DRAFTING INDONESIA - Lovika Augusta Purwaningtyas; Nur Husna (PARADIGMA PENGABDIAN, 2025)
This community service activity aims to meet the academic community's need for conceptual and practical understanding of regulatory drafting in the context of preparing the Draft Criminal Procedure Code (RKUHAP) as a national criminal procedure law draft. This need arises from the low literacy regarding the structure of legislation, particularly concerning norm formulation techniques, the organization of chapters and articles, as well as the harmonization principles that underpin the drafting of the RKUHAP. Empowerment efforts are carried out through workshops on the structural analysis of RKUHAP drafting, designed to provide a focused enhancement of knowledge on the principles of regulatory drafting in Indonesia. The implementation methods include material presentations, interactive discussions, demonstrations of article structure analysis, and assessments of understanding before and after the workshop. This approach is used to obtain empirical insights into the extent to which the workshop implementation is capable of meeting the regulatory literacy needs of the academic community. The results of the activity indicate a significant improvement in participants' understanding of the normative structure within the Draft Criminal Procedure Code (RKUHAP), including their ability to identify technical formulation weaknesses, systematic errors, and potential disharmony with other regulations. The workshop activities also strengthened participants' analytical skills in assessing the quality of a draft regulation based on regulatory drafting principles. The conclusion of this service activity emphasizes that the workshop implementation effectively enhances regulatory literacy and the competency of the academic community in understanding and evaluating the drafting of the RKUHAP. These findings highlight the need for the continuation of similar activities to broaden legislative literacy capacity in the academic environment.